Nanocomposites of iron oxide, sodium alginate, and eugenol induce apoptosis via PI3K/Akt/mTOR signaling in Hep3 cells and in vivo hepatotoxicity in the zebrafish model - Elderdery, Abozer Y.; Alzerwi, Nasser A.N.; Alzahrani, Badr; Alsrhani, Abdullah; Alsultan, Afnan; Rayzah, Musaed; Idrees, Bandar; Rayzah, Fares; Baksh, Yaser; Alzahrani, Ahmed M.; Alabdulsalam, Abdulrahim A.; Mohamedain, A.; et al. (Elsevier B.V., 2024)
Hepatic cancer is among the most recurrently detected malignancies worldwide and one of the main contributors to cancer-associated mortality. With few available therapeutic choices, there is an instant necessity to explore suitable options. In this aspect, Nanotechnology has been employed to explore prospective chemotherapeutic approaches, especially for cancer treatment. Nanotechnology is concerned with the biological and physical properties of nanoparticles in the therapeutic use of drugs. In the current work, formulation, and characterization of α-Fe2O3–Sodium Alginate-Eugenol nanocomposites (FSE NCs) using several approaches like SEM and TEM, UV–visible, FTIR, and PL spectroscopy, XRD, EDAX, and DLS studies have been performed. With an average size of 50 nm, the rhombohedral structure of NCs was identified. Further, their anticancer activity against Hep3B liver cancer cell lines has been performed by cell viability, dual staining, DCFH-DA, Annexin-V/-FITC/PI, cell cycle analysis methods, and PI3K/Akt/mTOR signaling proteins were studied to assess the anticancer effects of the NCs in Hep3B cells. Also, anti-cancer activity on animal modeling in-vivo using zebra fishes to hematological parameters, liver enzymes, and histopathology study effectiveness was noticed. Moreover, the NCs reduced the viability, elevated the ROS accumulation, diminished the membrane integrity, reduced the antioxidants, blocked the cell cycle, and triggered the PI3K/Akt/mTOR signaling axis that eventually resulted in cell death. As a result, FSE NCs possess huge potential for use as a possible anticancer candidate.